Design of Anti-Reflection Coatings for Application in the Infrared Region (10.6 micron) - Jabbar, Mushtak Abdulmohsen; Alwan, Tariq J. (Iraqi Journal of Science, 2020)
In this research, anti-reflection coatings consisting of single and double layers were designed in the IR (8 – 14μm) region to reduce the unwanted reflections of germanium (Ge) substrate. The reflectance of Ge substrate was about 36% per surface. These values were reduced reasonably by using single and double layer anti-reflection. The used layers were promoted in their performance by changing their thickness and refractive indices. The results indicated that the suggested structures are very efficient in reducing the reflectance of the Ge substrates in the selected region. The performance of the double layer antireflection coatings of ZnSe, BaF2 and BiF3 on Ge substrates is presented.